Nilai Pedagosis dalam Ritual Domyak - Anggy Giri Prawiyogi; Retno Dwimarwati; Suhendi Afryanto (PANTUN, 2022)
ABSTRACTDomyak is a ritual means of asking for rain at the foot of Mount Burangrang, Pasir AnginVillage, Darang District and Purwakarta Regency. In 1920, domyak was called chickpeas but in1990 it became domyak (ngadogdog and rampayak) meaning playing dogdog music with dances.This paper aims to examine the pedagogical values contained in the domyak ritual and the domyakritual process. The presentation is carried out in several stages which are also accompanied by severalforms of performing arts. The domyak ritual is performed in the form of helaran or procession orusing a stage. Bloom’s taxonomic theory is applied to explore pedagogical values in domyak rituals.Qualitative data were collected through observation, interviews, and documentation. The results ofthe study include the pedagogical values contained in the goals of education, educational content,and educational tools used. The purpose of education is that each of the member of the communitiesshould master traditional customs, especially in the domyak ritual to ask for rain; The contents ofeducation are ritual traditions which have been passed down from generation to generation fromthe 1920s to the present; Educational tools used in the form of habituation, supervision, orders,prohibitions and rewards in these ritual activities, such as: in starting the ritual by praying and thecommand to bathe the cat in the ritual activity.Keywords: Pedagogical value, domyak ritualABSTRAKDomyak merupakan sarana ritual meminta hujan yang berasal dari kaki GunungBurangrang Desa Pasir Angin Kecamatan Darangdan Kabupaten Purwakarta. Pada tahun1920 Domyak tersebut dinamakan buncis dan pada tahun 1990 berubah menjadi Domyakyang berarti (ngadogdog dan rampayak) bermain musik dogdog dengan tarian. Tulisan inibertujuan untuk mengkaji nilai-nilai pedagogis yang terdapat pada ritual Domyak sertaposes ritual domyak. Penyajiannya dilakukan dalam beberapa tahapan-tahapan yang jugadiiringi oleh beberapa bentuk seni pertunjukan. Ritual Domyak dipertunjukkan dalambentuk helaran atau arak-arakan maupun menggunakan panggung. Teori taksonomiBloom digunakan untuk menggali nilai-nilai pedagogis dalam ritual domyak. Datakualitatif dikumpulkan melalu observasi, wawancara, dan dokumentasi. Hasil Penelitianmencakup nilai-nilai pedagogis yang terdapat dalam tujuan pendidikan, pendidikan, isipendidikan serta alat pendidikan yang digunakan. Tujuan pendidikan yakni setiap wargamasyarakat harus menguasai adat tradisi terutama dalam ritual Domyak untuk memintahujan; Isi pendidikan yakni tradisi ritual yang diturunkan secara turun temurun dari tahun1920 sampai saat ini; Alat pendidikan yang digunakan berupa pembiasaan, pengawasan,perintah, larangan dan ganjaran dalam kegiatan ritual tersebut, seperti: dalam memulairitual dengan berdoa dan perintah untuk memandikan kucing dalam kegiatan ritualtersebut.Kata Kunci: Nilai pedagogis, ritual domyak